Terminology in trichology - Ashish Singh (Wolters Kluwer Medknow Publications, 2022)
"Terminology in Trichology" is a concise guide to the essential language of trichology. It has been written with the aim of making readers aware of commonly used terms in trichology. It has been structured in such a way that it should prove useful to the postgraduates and practicing dermatologists and trichologists. Terms are explained in simple language so that they are easy to understand, without including excessive details.